Prospects of the Bersukaria Walking Tours as Educative Tourism Activities in the Middle of Social Media Development - Savitri, Devita; Widisuseno, Iriyanto (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
Currently, the younger generation is confronted with the dynamics of social media development, which has various adverse outcomes, such as reduced social interaction, diminished moral values, and a restricted understanding of cultural and historical aspects. In this context, the Bersukaria Walking Tour emerges as a solution, offering an enjoyable learning experience while introducing cultural and historical heritage interactively and collaboratively. This research aims to assess the presence, prospects, and potential of the Bersukaria Walking Tour as a choice for educational tour activities for the younger generation. The research employed a mixed-methods approach, which involved collecting data through observations, interviews, surveys, and the analysis of documents. The gathered information was subsequently analyzed using a descriptive-qualitative approach. The findings indicate promising prospects for the Bersukaria Walking Tour among the younger generation, which can be categorized into two primary segments: students (62.80%) and young workers (65.70%). This clearly indicates the potential value of the Bersukaria Walking Tour as a beneficial educational tourism experience for them.